The tween television diet: a content analysis of US tween program food references. Issue 2 (3rd April 2018) - Hahn, Rachel; Aubrey, Jennifer Stevens
Abstract: This content analysis, grounded in social cognitive theory, examined the nutritional quality of food, the outcomes associated with consuming food, the characters who reference food, and the context of food on narrative tween (9–14 year olds) television programs shown on Disney, Disney XD, Nickelodeon, Teen Nick, and Cartoon Network in the 2004–2013 seasons. Nutritious foods were portrayed more frequently than non-nutritious foods, and the outcomes of consuming food were mostly neutral, followed by positive, and then negative outcomes. Attractive characters most frequently experienced positive outcomes for consuming nutritious foods, whereas average-looking characters most frequently experienced negative outcomes for consuming nutritious food. Significant two-way interactions were found for nutritional quality with both food purpose and food occasion. Results are discussed in light of the healthful messages portrayed on tween television and the potential for modeling effects among tweens.